THE IMPORTANCE OF INFORMATICS IN MANAGING MEDICAL DATABASES - Iroda Tolibjon qizi Yaxshiboyeva (Modern American Journals, 2026)
The study explores the significance of informatics in managing medical databases within modern healthcare systems. It highlights how digital tools, such as electronic health records (EHR), electronic medical records (EMR), and cloud-based databases, improve diagnostic accuracy, accelerate treatment processes, and enhance the efficiency of healthcare professionals. Despite challenges including limited technical infrastructure, insufficient staff training, and data security concerns, the integration of informatics is essential for achieving a patient-centered, efficient, and secure healthcare system. Recommendations for optimizing database management and ensuring data confidentiality are discussed.
Keywords: Medical databases, Informatics, Electronic Health Records, Data management, Healthcare efficiency, Data security.